1986
DOI: 10.1002/pdi.1960030513
|View full text |Cite
|
Sign up to set email alerts
|

Family histories in Asian and European non‐insulin‐dependent diabetic patients

Abstract: Family histories of 135 Asian Indian and 146 European NIDD patients attending clinics in Ealing and Hammersmith Hospitals were obtained, using a detailed questionnaire. Forty‐five per‐cent of Asian and 36% of European patients had a first‐degree relative with diabetes. Twenty‐eight per‐cent of Asians and 20% of Europeans had one diabetic parent. In 10% of Asians and 1% of Europeans, both parents were diabetic (p<0.01). Autosomal‐dominant inheritance was seen in 14% of Asians and 4% of Europeans (p<0.01). The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…34,35 However, in the present study, in the group with dysglycemia, family history of diabetes was not different from that of the group with high WC/ no dysglycemia. It has been shown that normal-weight individuals with dysglycemia have impaired first-phase insulin secretion compared with those with normoglycemia.…”
Section: Discussioncontrasting
confidence: 72%
“…34,35 However, in the present study, in the group with dysglycemia, family history of diabetes was not different from that of the group with high WC/ no dysglycemia. It has been shown that normal-weight individuals with dysglycemia have impaired first-phase insulin secretion compared with those with normoglycemia.…”
Section: Discussioncontrasting
confidence: 72%
“…Asian Indians have an ethnic susceptibility to Type II diabetes [16,17] and a high familial aggregation of the disease [18,19]. In ethnic groups such as the Naruans with high prevalence of Type II diabetes, a plateau seems to have been reached [20].…”
Section: Discussionmentioning
confidence: 99%
“…families [1][2][3][4][5][6][7] and monozygous twin studies [8,9]. It is now known that maturity-onset diabetes of the young (MODY) is an autosomal-dominant monogenic disease caused by a number of MODY genes [10].…”
Section: Introductionmentioning
confidence: 99%